Extended Stress–Strain Characterization of Automotive Steels at Dynamic Rates - Giuseppe Mirone; Raffaele Barbagallo; Michele Maria Tedesco; Daniele De Caro; Matteo Ferrea (Metals, 2022)
Demanding structural applications require a detailed knowledge of the materials response up to the very late stages before failure. Ductile high-strength steels may undergo pronounced necking over the majority of their straining life; this makes a reliable stress–strain characterization difficult, especially at dynamic rates, because the self-heating from fast adiabatic dissipation may promote thermal effects interplaying with the strain rate effects. Further complications arise in deriving the postnecking flow curves when the material is a metal sheet due to geometrical issues intrinsic in the prismatic flat shape of the specimens. This paper focuses on the experimental derivation of the flow curves of DP1000 and MS1700 steels at strain rates ranging from 1 to 500/s. In addition, the moderately high temperatures achieved due to the self-heating at dynamic rates are imposed at static rates for separately investigating thermal and dynamic effects. Digital Image Correlation (DIC) and pixel counting optical techniques are used together with postprocessing procedures based on standard criteria and on physical considerations proposed by the authors. The resulting hardening curves are compared to each other and the advantages of the proposed method are discussed.